Advanced multichannel submersible probe for autonomous high-resolution in situ monitoring of the cycling of the potentially bioavailable fraction of a range of trace metals. (November 2021) - Tercier-Waeber, Mary-Lou; Confalonieri, Fabio; Abdou, Melina; Dutruch, Lionel; Bossy, Cécile; Fighera, Marianna; Bakker, Eric; Graziottin, Flavio; van der Wal, Peter; Schäfer, Jörg
Abstract: We report here on the development and application of a submersible, compact, low power consumption, integrated multichannel trace metal sensing probe (TracMetal). This probe is unique in that it allows high-resolution, simultaneous in-situ measurements of the potentially bioavailable (so-called dynamic) fraction of Hg(II), As(III), Cd(II), Pb(II), Cu(II), Zn(II). The TracMetal incorporates nanostructured Au-plated and Hg-plated gel-integrated microelectrode arrays. In addition to be selective to the fraction of metal potentially bioavailable, they offer protection against fouling and ill-controlled convective interferences. Sensitivities in the low pM for Hg(II) and sub-nM for the other target trace metals is achieved with precision ≤ 12%. The TracMetal is capable of autonomous operation during deployment, with routines for repetitive measurements (1-2 h −1 ), data storage and management, data computer visualization, and wireless data transfer. The system was successfully applied in the Arcachon Bay, to study the temporal variation of the dynamic fraction of the trace metals targeted. The in situ autonomous TracMetal measurements were combined with in situ measurements of the master bio-physicochemical parameters and sample collection for complementary measurements of the dissolved metal concentrations, organic matter concentrations and proxy for biological activities. The integration of all data revealed that various biotic and abiotic processes control the temporal variation of the dynamic fractions of the target metals (Medyn ). The difference in the percentage of the dynamic forms of the metals studied and the short-term processes influencing their variation highlight the TracMetal potentiality as metal bioavailability-assessment sentinel to achieve comprehensive environmental monitoring of dynamic aquatic systems. Graphical abstract: Image 1 Highlights: Unique submersible autonomous multichannel tool for in situ metal quantification. Simultaneous detection of the bioavailable fraction of six hazardous metals. Autonomous monitoring of short-term temporal variation of bioaccessible metal species. Biotic and abiotic processes influencing the speciation of the trace metals targeted.